Rabbit on the run? A hitherto overlooked museum specimen of European rabbit Oryctolagus cuniculus, collected in Helsinki, Finland, in 1921 - Pihlström, Henry (Memoranda Societatis pro Fauna et Flora Fennica, 2016)
The European rabbit Oryctolagus cuniculus is an invasive species in Finland. It is, however, highly localized and populations are only found in urban and suburban areas in Helsinki and a few other larger cities. The current Finnish rabbit population originates from pets that escaped or were set loose. It is believed that feral rabbits did not become established in Helsinki until around the year 1985. Here is reported a rabbit specimen, consisting of a skin and a skull, which was collected in Helsinki in 1921. The specimen, which is housed in the Finnish Museum of Natural History, Hel-sinki, has been overlooked for nearly a century, due to the fact that it was originally misidentified as a European hare Lepus europaeus. The historical significance of this specimen is discussed.